The mining sectors in Chile and Norway, ca. 1870 - 1940: the development of a knowledge gap - Kristin Ranestad (European Historical Economics Society (EHES), 2016)
Chile and Norway are two 'natural resource intensive economies', which have had different development trajectories, yet are closely similar in industrial structure and geophysical conditions. The questions of how and why Chile and Norway have developed so differently are explored through an analysis of how knowledge accumulation occurred and how it was transformed by learning into technological innovation in mining, a sector which has long traditions in Norway and has by far been the largest export sector in Chile for centuries. Similar types of 'knowledge organisations' with the direct aim of developing knowledge for mining were developed in both countries. Formal mining education, scientifically trained professionals, organisations for technology transfer and geological mapping and ore surveys are compared in search of differences which may explain the underlying reasons for variations in economic growth.
Keywords: N30; N50; L72; 330; natural intensive economies; Chile; Norway; mining; innovation; mining education; technical education; knowledge organisations